COMPARISON OF ENDOSCOPIC PAPILLA BALLOON DILATATION AND ENDOSCOPIC SPHINCTEROTOMY IN THE TREATMENT OF CHOLEDOCHOLITHIASIS - NAKATA, Yutaka; NARUSHIMA, Michiki; TOMIOKA, Noriaki (Nihon Rinsho Geka Gakkai Zasshi (Journal of Japan Surgical Association), 2003)
Endoscopic papilla balloon dilatation (EPBD) has recently been evaluated in the treatment of choledocholithiasis. We report some advantages of EPBD in comparison to endoscopic sphincterotomy (EST). Subjects were 81 patients with choledocholithiasis. Of the 81 patients, 32 patients with EST before 1996 and 30 patients with EPBD after 1996. A choledochotomy without endoscopic treatment was performed in 19 patients. The successful rate of endoscopic treatment was 60% before 1996, but significantly increased to 86% since 1996. The frequency of mechanical lithotomy and endoscopic treatment to accomplish stone romoval were comparable between the EST and EPBD groups. Bile duct stones smaller than 10 mm in diameter and not exceeding 3 in the number were easyly removed with either a single EST session or EPBD session. The postoperative serum amylase level was significantly lower in the EPBD group, and moreover, serious complications such as massive bleeding or duodenal perforation which occurred after EST did not occur after EPBD. In coclusion, we recommend EPBD as the first choice of treatment for choledocholithiasis, because EPBD is less invasive than EST and can safely be performed in patients who are not candidates for EST.